A modified method for punctoplasty: “Excisional punctoplasty with the guidance of a 27 G Rycroft cannula” - Temizsoylu, Onur; Şahin, Gözde; Koçkar, Alev; Şengül, Alper; Yüzbaşıoğlu, Erdal (Journal of Surgery and Medicine, 2019)
Aim: We modified conventional 2-snip punctoplasty to ease procedure and to perform with simple equipment which is widely accessible in the operation rooms. Methods: This new procedure has been performed to 10 eyes of 6 patients. After the appropriate width has been provided, a 27G anterior chamber cannula which is actually manufactured for cataract surgery was inserted to punctum and pushed forward 2 mm vertically and 1 mm horizontally. After that, the surgeon exposed the tip of cannulas by opening conjunctiva with conjunctival scissors (Westcott Conjunctival Scissors) from the projection site of the tip of the cannula. The Rycroft cannula is used for better guidance for canaliculus anatomy instead of lacrimal cannulas. After canaliculus was hanged with the cannula, a conjunctival incision was made from the entrance of cannula to the punctum towards the point where the cannula exposed from conjunctiva via Westcott scissors. In the next step, two sides of the formed flap were held with toothed forceps orderly and were removed by cutting with conjunctival scissors. Results: After 6 month follow-up, none of the patients complained with epiphora and satisfied with the surgery. All participants have been defined with the presence of Grade 3-5 punctal aperture with the references of Punctum Size Grading by Slit-Lamp Examination. Conclusion: In this article, we could apply this method to a very limited number of patients and our follow-up (6 months) is relatively short to claim the re-stenosis ratio but in the immediate postoperative period, we didn’t encounter any re-stenosis.